Stimulus-Organism-Response (SOR) Paradigm in Country of Origin, Brand Experience, Customer Satisfaction, Brand Loyalty: The National Cultural Inheritance Matters - Kristanti, Maria Mia (Universitas Airlangga, 2025)
Indonesia, with its rich cultural heritage and philosophy, has many traditional art patterns and techniques on fashion, especially Batik, which UNESCO declared a Masterpiece of the Oral and Intangible Heritage of Humanity in 2008. However, global competition is eroding this ancient legacy, as modern consumer behavior tends to prefer foreign products. Brand experience has emerged as a source of customer satisfaction and loyalty. Hence this valuable experience motivating customers to embrace the national heritage as a major part of the country’s identity on a daily basis. The cultural heritage of Batik plays a key role in shaping their identity. Despite the growth of stalls and the fading country of origin image of Batik, it is crucial to maintain the national heritage product. This study aims to analyze the relationship between product authenticity as a country of origin and brand experience offerings on customer satisfaction and brand loyalty to sustain the national heritage product. The target population consists of customer of Batik, aged at least 17 years old, who have purchased at least two pieces in the last six months at a high price point of branding. The research methodology involves SEM-PLS with purposive sampling technique. The results of the descriptive indicator scores indicate that brand experience influences brand loyalty through visual appearance, and customer satisfaction is influenced by proper brand experience that evokes customer’ set. The country of origin influences customer satisfaction through brand experience, as Indonesia’s country of origin for Batik shapes customer brand associations. Additionally, brand experience influences brand loyalty through customer satisfaction via ethnocentric consumer attitude, and the country of origin affects brand loyalty through brand experience as a catalyst for brand purchase intention leveraging Indonesia’s international heritage reputation as the origin of Batik in global competition.